Office myringoplasty by chemical cauterization and paper patching: a prospective study - Upreti, Garima (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Surgery for tympanic membrane perforation entails its own morbidity, risk of anesthesia, psychological trauma, along with long waiting periods for patients, especially in a tertiary care centre like ours. The purpose of this study was to evaluate outcomes of chemical cauterization and patching of perforation, performed as an office procedure in select cases. Methods: The study was conducted in a tertiary hospital from January 2016 to December 2017. The patients were selected based on the inclusion criteria, after thorough clinical assessment, examination under microscope and pure tone audiogram. All cases underwent cauterization of margins of perforation using 10% trichloroacetic acid (TCA), followed by patching with appropriately sized pre-sterilized cigarette paper patch. The patients were followed up weekly till the perforation was completely healed or till 12 weeks. If required, the procedure was repeated. Results: 68 cases were included in the study. Most common site of perforation was antero-inferior quadrant of pars tensa. Most common etiology was inflammatory. Number of applications ranged from 1 to 3. The procedure was successful in 62 cases (91.2%). All cases with traumatic perforation, residual perforation post-surgery and persistent perforation after grommet extrusion healed well. All 6 cases with treatment failure had inflammatory etiology, 4 involving postero-superior quadrant. Conclusions: In patients with small, central, dry perforation of tympanic membrane, chemical cauterization using TCA and paper patching can yield results comparable to that of surgery, while abating the morbidity and psychological trauma of surgery and saving time for both patient and doctor.